KARAKTERISASI SECARA RINCI SENYAWA HETEROATOM DALAM FRAKSI RINGAN MINYAK BATUBARA TANITO HARUM DAN PRODUK MINYAK HASIL HYDROTREATMENT - Sri Djangkung Sumbogo Murti; Lambok Hlarius Silalahi (Badan Pengkajian dan Penerapan Teknologi, 2007)
Heteroatom compounds contained in coal oil Tanito Harum both before and afterhydrotreatment were identified using a gas feed chromatography with atomicemission detector (GC AED). Alkylated dibenzothiophenes benzothiophenes andsulfur compounds were found to be dominant in the original faction, his wholesuccessfully removed through hydrotreatment process on the condition of 350oC,10 MPa, and 60 min. Alkylated anilines, quinoline, indoles, and carbazoles foundin the original oil as nitrogen compounds. Two types of specific nitrogencompounds persist for hydrotreatment process underway and identifiedrespectively as C11H20N and C14H23N, based on the ratio of the element iscalibrated by GC-AED and the molecular weight was measured by GC-MS (massspectrometry). The empirical formula is very similar to such C11H19N andC14H23N, were detected by MS and NMR after concentrated by extraction. Somesulfur compounds present in non-aromatic fraction, while all nitrogen compoundsare completely concentrated in the aromatic fraction after separation byconventional chromatographic columns. There was also alkylated phenols,benzofurans and dibenzofurans were found as typical oxygen compounds in theoil.Kata Kunci: limonite catalyst; coal liquefaction, catalytic hydrotreating, liquefiedcoal oil, gas oil fraction, cetane index, octaen number